Trade Openness, Economic Growth and Unemployment Reduction in Arab Region - Awad-Warrad, Taleb (International Journal of Economics and Financial Issues, 2018)
The main objective of this research paper is to empirically evaluate the theoretical relationship between unemployment and some key macroeconomic determinants including among others trade openness policy and real economic growth for Arab countries. The main question of the study is whether achieving economic growth and liberalizing international trade contribute to creating more jobs and hence resulting in less unemployment. The study utilizes a cross time series sample coving the period 1990-2015 for seven selected Arab countries. The study estimated the unemployment model using panel WLS. The study provides evidence of large and significant impact of trade openness on unemployment rates in the selected Arab countries when taken as one pooled group. On the other hand, as expected real economic growth affected favorably unemployment rates in this group of countries. Keywords: trade openness, real growth, unemployment, Arab countries. JEL Classifications: E24, F1, F43